Distinction between antinuclear antibody and P-ANCA. Issue 11 (November 1991) - Lee, S S; Lawton, J W; Chak, W
Abstract : To differentiate between perinuclear immunofluorescence staining of antinuclear antibody (ANA) and the perinuclear form of anti-neutrophil cytoplasmic antibody (P-ANCA), the pattern after formaldehyde vapour fixation of normal human neutrophils was compared with that of standard ethanol fixation. Fifteen out of 17 myeloperoxidase antibody positive sera showed cytoplasmic staining on formaldehyde vapour fixed cells; 30 of the 32 ANA positive samples became negative or gave weak nuclear staining on the same substrate. Formaldehyde vapour fixation is a simple, useful technique for differentiating between ANA and P-ANCA.